Iron-Based Superconductivity - Johnson, Peter D.; Xu, Guangyong; Yin, Wei-Guo (Springer Series in Materials Science,, 2015)
This volume presents an in-depth review of experimental and theoretical studies on the newly discovered Fe-based superconductors. Following the Introduction, which places iron-based superconductors in the context of other unconventional superconductors, the book is organized into three sections covering sample growth, experimental characterization, and theoretical understanding. To understand the complex structure-property relationships of these materials, results from a wide range of experimental techniques and theoretical approaches are described that probe the electronic and magnetic properties and offer insight into either itinerant or localized electronic states. The extensive reference lists provide a bridge to further reading. Iron-Based Superconductivity is essential reading for advanced undergraduate and graduate students as well as researchers active in the fields of condensed matter physics and materials science in general, particularly those with an interest in correlated metals, frustrated spin systems, superconductivity, and competing orders. Provides a detailed description of sample growth and characterization for correlated and complex materials Features extensive coverage of results from major experimental techniques that probe the electronic and magnetic properties of Fe-based superconductors Offers a comprehensive review of recent theoretical developments in electronic correlation and frustration Represents a one-stop reference for a broad audience from advanced undergraduate and graduate students through active researchers Written by leading experts in each of the relevant sub-fields.